Superior Enhancement of Cutaneous Microcirculation Due to “Cyclic” Application of a Negative Pressure Wound Therapy Device in Humans – Local and Remote Effects - Sogorski, Alexander; Becker, Amira; Dadras, Mehran; Wallner, Christoph; Wagner, Johannes Maximillian; Glinski, Maxi v; Lehnhardt, Marcus; Behr, Björn (Frontiers in Surgery, 2022)
Objectives Despite a common utilization of “Negative Pressure Wound Therapy” (NPWT) Devices in a wide range of specialties, some of the basic mechanisms of action of the techniques are still on debate. Conflicting results from prior studies demonstrate our lack of understanding how wound-bed perfusion or cutaneous microcirculation is affected by NPWT. Methods We conducted a prospective randomized study which included 45 healthy subjects to further investigate the acute effects of NPWT on cutaneous microcirculation underneath the applied dressing. Three modes of application, namely, continuous, intermittent, cyclic, were tested. Amongst others, measurements of elicited surface pressure and a comprehensive microcirculatory analysis were carried out by utilizing an O2C-device. For the detection of (systemic) remote effects, perfusion changes of the contra-lateral thigh were evaluated. Results All three tested modes of application led to a significant (p < 0.05) improvement in local tissue perfusion with an increased blood flow of max +151% and tissue oxygen saturation of +28.2% compared to baseline values. Surface pressure under the dressing significantly increased up to 29.29 mmHg due to the activation of the NPWT device. Continuous, intermittent, and cyclic application of negative pressure were accurately sensed by participants, resulting in reported pain values that mirrored the different levels of applied suction. Although the cyclic application mode showed the most pronounced effects regarding microcirculatory changes, no statistical significance between groups was observed. Conclusion We could demonstrate a significant improvement of cutaneous microcirculation under an applied NPWT dressing with favorable effects due to cyclic mode of application. An increased surface pressure leads to a better venous drainage of the tissue, which was shown to increase arterial inflow with a consecutive improvement of oxygen supply. Further research is warranted to evaluate our findings regarding wound bed perfusion in the clinical field with respect to formation of granulation tissue and wound healing.